Optimizing Instagram Branded Content: Increase Purchase Intention through Brand Loyalty on Local Clothing Brand - Handayani, Yuliasti Ika; Erwita, Monica Adjeng; Kristanti, Mevi Yolanda (Universitas Islam Nahdlatul Ulama Jepara, 2025)
Objective: This study aims to examine the influence of branded content on Instagram on consumer purchase intention in local clothing brands, with a specific focus on the mediating role of brand loyalty. By understanding this relationship, the research provides insights into how businesses can optimize their digital marketing strategies to drive customer engagement and sales. Research Design & Methods: A quantitative approach was employed, collecting survey data from 230 respondents who are active Instagram users residing in East Java and who actively engage with local clothing brands on the platform. Statistical analysis was conducted using SPSS to test the relationships between branded content, brand loyalty, and purchase intention, ensuring data validity and reliability. Findings: The results indicate that branded content on Instagram positively influences brand loyalty. Brand loyalty significantly enhances consumer purchase intention. Engagement with branded content strengthens emotional connections with the brand, leading to higher purchase likelihood. Implications and Recommendations: Local clothing brands should invest in high-quality branded content and leverage interactive features like Instagram Stories, Reels, and influencer collaborations to strengthen consumer connections and boost brand loyalty. Continuously tracking consumer responses will help refine content marketing strategies for optimal engagement and impact. Contribution & Value Added: This study provides empirical evidence on the role of Instagram-branded content in shaping consumer behavior. It highlights the importance of brand loyalty as a key driver of purchase intention, offering actionable insights for marketers looking to strengthen their brand presence in the digital landscape.